Implementation of Character Education in Islamic Boarding Schools: Implementasi Pendidikan Karakter di Pondok Pesantren - Mochamad Choirur Rozikin; Anita Puji Astutik (Universitas Muhammadiyah Sidoarjo, 2021)
This research was conducted based on the application of character education in Islamic boarding schools. Islamic boarding school is the oldest education in Indonesia. In general, Islamic boarding schools emphasize Islamic religious education. And in terms of education, of course, the main characteristic is about character education. Every educational institution has its own way of educating students or students in character education. And the Ahlusshofa Wal Wafa Islamic Boarding School is intended as the object of research. Therefore, based on this background, the authors formulate the following problems: How is the implementation in the Ahlusshofa Wal Wafa Islamic boarding school? How is Syiir Tanpo Watton as a source of character learning?